GROWTH PERFORMANCE, BODY WEIGHT PREDICTION AND HAEMOTOLOGICAL INDICES OF RABBITS FED RUMEN LIQUOR FERMENTED SUGARCANE SCRAPPING MEAL - Abdullahi, Hudu Ramalan; Dogara, Muhammad Umar; Itodo, Joy Iyojo; Musa, Muhammad Makama (FUDMA Journal of Sciences, 2024)
The study aimed to assess the impact of incorporating rumen liquor sugar cane scrapping meal (RLFSCSM) into rabbit diets on growth performance, body weight and haemotological indices. A total of 24 mixed breed grower rabbits of similar live weight (700 – 832g) were used and subjected to a Completely Randomized Designed (CRD) with 4 treatments, 3 replicate having 2 rabbits each. The rabbit diets were formulated to replace maize at different percentages 0, 10, 20 and 30% representing T1, T2, T3, and T4 respectively. Feeding and other routine management practices were strictly adhered to according to standard practices throughout the experimental period. The results showed a p<0.05 increase in the total weight gain (676.83g/rabbit), average daily gain (19.34 g/rabbit) and average daily feed intake (73.29g/rabbit). Additionally, Logistics 3P and Gompertz 3P predicted the highest growth rate of rabbits 935.599 and 935.582 g/rabbits at the age of 3 weeks. However, haematological parameters showed mixed effects, with a decrease in hemoglobin (10.77 to 10.50g/dL) and packed cell volume (35.50 to 33.66%) at certain inclusion levels of RLFSCSM but increases at higher levels. Red blood cell count remained relatively stable across treatments, while mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration improved (21.67 pg and 31.67 g/L) with increasing RLFSCSM levels. White blood cell counts and mean corpuscular volume were unaffected by RLFSCSM inclusion. It was concluded that diet containing 30% RLFSCSM could improve general performance and health without detrimental effects when fed to grower rabbit.